Inheritance Law in Egypt, Sudan, and Jordan: A Comparative Study of Systems and Implementation - Kandriana, Muhammad; Sukardiawan, I Wayan; Rifaid, Muhammad; Arifin, Zainal; Wildan, Muhammad; Zuhrah (Al-Risalah, 2025)
Inheritance law in Islamic legal systems exhibits unique characteristics shaped by religious doctrine, state policies, and socio-cultural dynamics. This study conducts a comparative analysis of inheritance law in Egypt, Sudan, and Jordan, focusing on legal sources, regulatory implementation, and practical challenges. By employing a normative juridical approach with comparative legal analysis, this research systematically examines legislation, court rulings, and scholarly literature to highlight variations in the application of Islamic inheritance principles across these jurisdictions. The findings reveal that while all three countries base their inheritance systems on Islamic law, significant differences emerge due to political, social, and cultural influences. Egypt integrates Islamic inheritance law with national regulations, reflecting modernization efforts, whereas Sudan maintains a fiqh-based system strongly influenced by customary law. Jordan, meanwhile, codifies Islamic inheritance law within its legal framework, with the Sharia Court playing a central role in dispute resolution. The comparative approach of this study underscores the adaptability of Islamic inheritance law in different legal environments and highlights the need for harmonization between religious principles and contemporary legal reforms. The findings carry important implications for future legal reforms, suggesting that policymakers should consider contextual adaptations to enhance inclusivity and responsiveness to social changes. This study contributes to comparative legal scholarship by offering insights into the dynamic interplay between Islamic law and national legal systems, while proposing recommendations for progressive inheritance law reform in Muslim-majority countries.